The Barangay 92 Apitong Health Center's Compliance to the Standards of Health Centers set up by the Department of Health and related authorities. - Carias, Jasper M. (Tacloban City Jasper Carias, 2011)
Barangay 92 Apitong is one of the Barangays of the Highly Urbanized City of Tacloban. A city should have adequate health facilities. Health centers and Hospitals are some of the needs that any city should have to be able to meet the needs of the people. Having a health center is one thing, making sure that the health center complies with the standards of duly recognized authorities is another. In the context of this research, compliance to standards entails being able to meet the requirements in the area of medical equipment, medical supplies, physical infrastructure, personnel and the like. The author of this study conducted this evaluation to determine if the health center complies with the standards set up by the DOH.
The standard of the DOH is the new PhilHealth Benchbook Standards for Outpatient Services. This PhilHealth Benchbook Standards for Outpatient Services covers Barangay Health Centers and Rural Health Units. By complying with the Philhealth Benchbook Standards for Outpatient Services, health centers could be accredited by the PhilHealth and could benefit tremendously from the standards set up by the DOH since the quality of health care service will be better and the health center will be well equipped. The result revealed that the Barangay 92 Apitong Health Center does not comply with the PhilHealth Benchbook Standards for Outpatient Services, specifically on the aspect of Medical equipment and Medical supplies that a Barangay Health Center should have. The midwife who is assigned to the center admitted that the center has a pressing need for improvement.
The analysis would suggest that there should be enough funding for the health center so that it would have sufficient, equipment and supplies. The analyses also clearly indicate the need of the local government officials and the DOH cooperation. The DOH should extend its technical expertise to the different LGU's. But hopefully, the health center should be prioritized highly by the Barangay officials and their plans for improvement must come to reality.
The findings of this study would be crucial since it can give the authorities the ideas on how to improve the health care facilities quality and be sensitive to its needs.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science